Effectiveness of Training Programs at the Gorontalo City Small and Medium Enterprises (LLK-UKM) Job Training Workshop - Iwan Adam; Fenti Prihatini Tui; Romy Tantu (PROVIDER JURNAL ILMU PEMERINTAHAN, 2024)
This research aims to describe (1) the effectiveness of training activities at the Small and Medium Enterprises Job Training Workshop (LLK-UKM) in Gorontalo City and (2) Determining Factors for the Effectiveness of Training Activities at the Gorontalo City Small and Medium Enterprises Job Training Workshop (LLK-UKM). . The research method used in this research is a research method with a qualitative approach. Data collection techniques were carried out using interviews, observation and documentation. The research results show that first, the effectiveness of the training program at the Gorontalo City Small and Medium Enterprises Job Training Workshop (LLK-UKM) can be seen from 1) Understanding the program. 2) Right on target, 3) On time, 4) Achievement of goals 5) Real change. Of these 5 aspects, there is one aspect that is not yet effective, namely understanding the program. The process of disseminating information has not been effective, resulting in some people not knowing about the training program organized by LLK-UKM Gorontalo City. Second, the effectiveness of the training program at the Gorontalo City Small and Medium Enterprises Job Training Workshop (LLK-UKM) can be seen from two aspects, namely: (1) Human resources and (2) Infrastructure. The research results show that these two factors are not effective. The lack of instructors available at LLK UKM Gorontalo City is hampering training activities. Likewise, the second factor is inadequate infrastructure. Apart from the very limited amount of equipment available, most of it is still manual equipment.